A novel feature extraction technique for the clustering of SNP data: A novel feature extraction technique for the clustering of SNP data - RAJESH DWIVEDI; ARUNA TIWARI; NEHA BHARILL; MILIND RATNAPARKHE (Journal of Oilseeds Research, 2023)
In this work, we proposed a novel feature extraction technique for the Single NucleotidePolymorphism (SNP) data, which converts an SNP sequence into the numerical form. Later, we performed the clustering analysis on the feature vectors to group similar SNP sequences in one group.